O crédito rural para mulheres do semiárido norte-mineiro: um estudo do PRONAF no município de Porteirinha/MG, no período de 2005 a 2018 - Cleonice Elias dos Santos (2020)
Family farming has a fundamental role for rural development, being one of the pillars of the Brazilian agricultural sector, which presumes the importance of public policies aimed at the sector. The concept of family farming was adopted by the State in the 1990s, in a context of formulating public policies, mainly rural credit, such as Pronaf, which was specifically designed for the sector. The study aims to understand the effects of Pronaf, as a rural credit policy, on the lives of farmers in the semi-arid north of Minas Gerais, in the municipality of Porteirinha. The general objective is to analyze the perception of female farmers living in the municipality of Porteirinha-MG about the changes that occurred in the socioeconomic situation, as well as in gender relations and female empowerment, due to having been awarded with credits from Pronaf. The study was based on information from semi-structured interviews applied to a universe made up of representatives of institutions involved in the operation of Pronaf in Porteirinha and women benefiting from the Program in two rural communities in the municipality. At the institutional level, it was found that there was a lack of strategies to guarantee the effectiveness of Pronaf, especially Pronaf Mulher, such as the resistance of financial agents to direct credit with women as owners of the operation. According to the perception of the representatives of the institutions, there was socioeconomic and productive inclusion, improved property and increase in income, but there was no consensus regarding possible improvements in gender relations and female empowerment. In the perception of the beneficiary women, Pronaf enabled an increase in female participation, but women's autonomy in relation to productive activities and the use of financial resources is still restricted. Pronaf was able to improve gender equity, but several advances are needed, given that socio-cultural principles serve as obstacles for obtaining women's rights. On the socioeconomic level, improvements in income, in purchasing power, productivity and insertion in the local market are undeniable. In general, Pronaf proved to be relevant for the development of family farming, but there is a need for advances in other dimensions, such as socio-cultural issues, which are difficult to change. On the other hand, it was revealed that, based on the perception of the interviewed women farmers, female empowerment is a process under construction and for Pronaf to promote greater reflections on this process, practices and mediations aimed at this purpose are necessary.